SYSTEMATIC REVIEW: DETERMINANTS OF PATIENT SATISFACTION WITH HOSPITAL SERVICES - Adi, Ni Putu Deni; Ilyas, Yaslis (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Satisfactory and quality service will shape patient or customer loyalty, and satisfaction is closely related to